Increasing Knowledge of Residents in Pinang Griya Permai Housing in Waste Management through Training of Organic and Anorganic Waste Recycling by the Teratai Waste Bank - Indra; Syafrullah, Muhammad; Rahayu, Sri; Saputro, Heru; Saputra, Rilo Anggoro; Bagaskoro, Muhammad Akbar; Fauzan, Rubi Ahmad; Fatayati, Fitri Nur; Sabasteo, Jeremy Noel (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Garbage is currently still a problem for the community where there is a lack of knowledge of waste management properly. The waste bank is present as a solution to assist the government in reducing the accumulation of waste and helping to improve the economy of housewives, especially residents affected by the COVID-19 pandemic. Bank Sampah Teratai (BST) is one of the social group organizations engaged in environmental economics, especially in managing household waste for residents of RW. 05 Pinang Griya Permai, Pinang - Tangerang. Bank Sampah Teratai located in Pinang Griya Permai Tangerang is a partner in this activity. Observation results show that Bank Sampah Teratai does not yet have adequate knowledge in waste management, both organic and inorganic. Based on the above problems, a community partnership program was formed with the academic community (lecturers and students) of Universitas Budi Luhur to help solve problems at the Bank Sampah Teratai. Based on these conditions, training on organic and inorganic waste management was carried out for residents of the Pinang Griya Permai housing. This training provides understanding, and appropriate skills, which help residents to carry out organic and inorganic waste management. Based on the results of the questionnaire after the training was carried out, 100% of participants stated that the material presented was in accordance with their needs, and the material presented was also considered good by 100% of the participants. The long-term result of this training is an increase in the understanding and skills of the residents to manage organic and inorganic waste. This training has been a useful contribution to improving skills for members of the Bank Sampah Teratai in particular, and skills for residents of Pinang Griya Permai housing in general.